Inhibition of bacterial quorum sensing (general concept) - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2019)
The scientific review outlines current data characterizing the main provisions on the functioning of the mechanism of the sensory quorum in the system of interbacterial communications. A general characteristic of various compounds possessing an overwhelming influence on quorum sensory is presented. It is emphasized that the mechanism of sensory quorum inhibition is represented by three functional groups: a group of substances that suppress the activity of autoinducer synthases; a group of substances that block the autoinducer receptors; a group of substances that interfere with autoinducers interaction with their specific receptor.